Simulating the sensitivity of maize crop propagation to seasonal weather change (2011)
The paper simulmates the sensitivity of maize crop yield response to temperature increase with appropriate irrigation scheduling that may obviate the negative impact of temperature increase on crop yield. The model was run with weather records from International Institute of Tropical Agriculture (IITA) Ibadan for the period 2000 to 2008 with the yearly weather records divided into quarterly records depicting maize crop growth seasons from planting to harvesting. Quarterly growth seasons of January -May (I), May - September (II), September- January (III), seasons respectively for maize crop were considered. Simulation results were analyzed using the SPSS statistical tool and the method of Least Square Deviation (LSD). The study revealed that an increase in the average temperature by 1°C, 2°C and 3°C for the growth seasons results in average yield reduction. Average yield reduction ranges were 5.3%-8.7% (season-I), 0% (season-II) and 0.5%-1.7% (season-III) when irrigation was done at interval of 3 days; 6.1%-8.4%(season-I) 0%(season-II) and 1.7%-0.8%(season-III) when irrigating at critical depletion of 2mm water application depth and at rainfed condition; 17%- 21%(season-1), 0%(season-II) and 3.6%-7.2%(season-III) respectively. This shows that in season-II, temperature rise has no effect on maize yield due to the availability of rainfall at optimum growth condition. However, temperature negatively impacted on the yield of maize crop in seasons I and III with little or no rainfall. Hence, interval of 3 days and 2mm water application depth is best suitable under the study conditions for the three seasons